Management of acute respiratory distress syndrome: a challenge to modern medicine - Ngow, Harris Abdullah; WMN, Wan Khairina (OMICS Group, 2014)

(untitled)
Acute Respiratory Distress Syndrome (ARDS) is an acute inflammatory pulmonary injury in which marked oedema of the lungs causing progressive impairment of gas exchange, atelectasis, and decreased lung compliance. Over the years, several innovative methods to control the lung injury had been studied. Improvement in ventilation strategy has resulted in reduce mortality is ARDS patients. Meanwhile, adjunctive therapies such as inhaled nitric oxide, exogenous surfactant administration, patient positioning and immune-nutrition are other methods which may further improve the outcome of this condition. This case illustrates the use of multiple modalities of treatment which were useful in infant with this condition and a review of these treatment modalities.